2006
DOI: 10.1007/s10593-006-0142-y
|View full text |Cite
|
Sign up to set email alerts
|

Basicity of 2-phenyl-5-R-1,3,4-oxadiazoles

Abstract: CF 3 ) in aqueous sulfuric acid solutions. These compounds are weak organic bases . The values of pK BH + determined on the H 0 and X acidity function scales agree well with each other. The substituent at the 5 position has a substantial effect on the basicity of the 1,3,4-oxadiazole ring.Compounds of the 1,3,4-oxadiazole series are widely used in various areas of modern technology [1]. Considering the unique luminescent spectral properties of aryl-substituted 1,3,4-oxadiazoles and their ability to form stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…1,2,5-Oxadiazoles have unique physical and electronic properties relative to the 1,2,4- and 1,3,4-isomers . Differences in lipophilicity, basicity, and magnitude of the dipole moment ,, are observed (Figure ). Furazans are highly inductive, comparable to a trifluoromethyl or tetrazolyl group ,, (Figure ).…”
Section: Physical Propertiesmentioning
confidence: 95%
“…1,2,5-Oxadiazoles have unique physical and electronic properties relative to the 1,2,4- and 1,3,4-isomers . Differences in lipophilicity, basicity, and magnitude of the dipole moment ,, are observed (Figure ). Furazans are highly inductive, comparable to a trifluoromethyl or tetrazolyl group ,, (Figure ).…”
Section: Physical Propertiesmentioning
confidence: 95%
“…It was observed that the presence of two phenyl rings considerably increases the observed λ max value. For example, 2-phenyl-1,3,4-oxadiazole (14) has a λ max = 245 nm, 34 whereas the 2,5-diphenyl-1,3,4-oxadiazole (15) analogue has a λ max = 276 nm ( Figure 7). 35 The analysis of UV spectra information allows us to infer that 1,3,4-oxadiazoles have greater aromaticity, presumably because of their symmetry.…”
Section: Differences Between 124-and 134-oxadiazolesmentioning
confidence: 99%
“…43 It is also possible to find protocols employing ultrasound irradiation to synthesize 1,2,4-oxadiazoles (29), as reported by Bretanha et al 44 Short reaction times (15 min) and high yields (84-98%) were reported for the reaction between trichloroacetoamidoxime (27) and the properly substituted benzoyl chlorides (28) in ethyl acetate as solvent (Scheme 4). 44 In a different approach, Yoshimura et al 45 reacted nitrile oxides (34) and nitriles (31) to obtain 1,2,4-oxadiazoles (32). Hydroxy(aryl)iodonium (IBA-OTf, 33) was employed allowing the formation in situ of nitrile oxides (34) from the respective nitriles (31).…”
Section: Differences Between 124-and 134-oxadiazolesmentioning
confidence: 99%
See 1 more Smart Citation